Photoelectrochemical biosensor based on SiW12@CdS quantum dots for the highly sensitive detection of HPV 16 DNA - Cheng, Yao; Sun, Chaoyue; Chang, Yuhua; Wu, Jiayin; Zhang, Zhihao; Liu, Yunqing; Ge, Shenguang; Li, Zhao; Li, Xiao; Sun, Liang; Zang, Dejin (Frontiers in Bioengineering and Biotechnology, 2023)
A highly sensitive biosensor for detecting HPV 16 DNA was prepared based on Keggin-type polyoxometalate (SiW12)-grafted CdS quantum dots (SiW12@CdS QDs) and colloidal gold nanoparticles (Au NPs), which exhibited remarkable selectivity and sensitivity upon target DNA detection because of its excellent photoelectrochemical (PEC) response. Here, an enhanced photoelectronic response ability was achieved with the strong association of SiW12@CdS QDs by polyoxometalate modification, which was developed through a convenient hydrothermal process. Furthermore, on Au NP-modified indium tin oxide slides, a multiple-site tripodal DNA walker sensing platform coupled with T7 exonuclease was successfully fabricated with SiW12@CdS QDs/NP DNA as a probe for detecting HPV 16 DNA. Due to the remarkable conductivity of Au NPs, the photosensitivity of the as-prepared biosensor was improved in an I3−/I− solution and avoided the use of other regents toxic to living organisms. Finally, under optimized conditions, the as-prepared biosensor protocol demonstrated wide linear ranges (15–130 nM), with a limit of detection of 0.8 nM and high selectivity, stability, and reproducibility. Moreover, the proposed PEC biosensor platform offers a reliable pathway for detecting other biological molecules with nano-functional materials.